Determinants of Lecturer Performance and Lecturer Career Development at Muhammadiyah Universities in Eastern Kalimantan - Vera Anitra; Djoko Setyadi; Sri Mintarti; Doddy Adhimursandi (Migration Letters, 2023)
Objective: Higher Education is an optional final stage in formal education, both in the form of Universities, Colleges, Polytechnics, Institutes and Academies, as well as one of the instruments of national education, which is expected to become a center for organizing and developing higher education as well as maintaining, fostering and developing science, technology, arts, and as a center for human resource development which is the spearhead in preparing human resources to be able to compete. Theoretical framework: The study aims to analyze and prove the influence of competence motivation, organizational culture, and work environment on lecturer performance and career development of lecturers at the Muhammadiyah University of East Kalimantan Region and place gender to find differences between male and female lecturers in the relationship between the influence of these variables. Method: This research uses a survey technique by distributing questionnaires, then the data or information obtained is processed by statistical methods using SmartPLS software. This explanatory research aims to test a theory or hypothesis to strengthen or reject a pre-existing theory or research hypothesis. The population in this study were lecturers at Muhammadiyah Universities in East Kalimantan, namely Muhammadiyah University of Berau (UM Berau) and Muhammadiyah University of East Kalimantan (UMKT), with the criteria that lecturers already have NIDN, working period ≥ 1 year, and lecturers are not currently on study assignment status. The data collection technique used a questionnaire with a Likert scale, and the data analysis technique used the Partial Least Square (PLS) approach and also conducted Multigroup Analysis to explore more in-depth information. The PLS method and Multigroup Analysis were chosen to comprehensively understand the relationship between the variables tested in this study. Results and conclusion: The results showed that motivation has no significant effect on lecturer performance or career development. Besides, there is a significant difference between female and male lecturers in the effect of motivation on lecturer performance. Still, there is no significant difference between female and male lecturers in the effect of motivation on career development. Competence has a significant effect on lecturer performance and career development. Besides, there is no significant difference between female and male lecturers in the effect of competence on lecturer performance. Still, there is a significant difference between female and male lecturers in the effect of competence on career development. Organizational culture has no significant impact on lecturer performance or career development. Still, there are significant differences between female and male lecturers in the influence of organizational culture on lecturer performance, and there are significant differences between female and male lecturers in the influence of organizational culture on career development. Work environment has a significant effect on lecturer performance on career development. In addition, there is a significant difference between female and male lecturers in the effect of work environment on lecturer performance. Still, there is no significant difference between female and male lecturers in the effect of work environment on career development. Lecturer performance has an insignificant impact on the career development of lecturers at Muhammadiyah University in the East Kalimantan Region. Implications of the research: This research has implications for developing Management Science, especially human resource management related to motivation, competence, organizational culture, work environment, lecturer performance and lecturer career development. Originality/value: Recognition and appreciation of academic achievements and lecturers’ contributions to increase motivation and developing competence in pedagogical skills and personality skills to improve career development, and there are differences in the career development performance of female and male lecturers.